2022
DOI: 10.1021/acsami.1c24569
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive Hydrogel Incorporating Prussian Blue Nanoparticles Promotes Diabetic Wound Healing via ROS Scavenging and Mitochondrial Function Restoration

Abstract: Diabetic foot ulcer is a serious complication in diabetes patients, imposing a serious physical and economic burden to patients and to the healthcare system as a whole. Oxidative stress is thought to be a key driver of the pathogenesis of such ulcers. However, no antioxidant drugs have received clinical approval to date, underscoring the need for the further development of such medications. Hydrogels can be applied directly to the wound site, wherein they function to prevent infection and maintain local moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 61 publications
0
78
0
1
Order By: Relevance
“…Superoxide dismutase (SOD) is a critical antioxidant enzyme in cells; it can catalyze the decomposition of O 2 − into O 2 and H 2 O 2 [ 50 ]. The SOD mimetic activity of the CeO 2 @PAA@RGD was evaluated using the WST-8 method.…”
Section: Resultsmentioning
confidence: 99%
“…Superoxide dismutase (SOD) is a critical antioxidant enzyme in cells; it can catalyze the decomposition of O 2 − into O 2 and H 2 O 2 [ 50 ]. The SOD mimetic activity of the CeO 2 @PAA@RGD was evaluated using the WST-8 method.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 showed that MPB had satisfied effect in promoting fibroblast proliferation. Previous reports have proved that PB nanoparticles could promote the activity of fibroblast cells and have a positive effect on collagen deposition during soft tissue healing 48,49) . Our results also suggested that MPB had satisfied effect in promoting fibroblast proliferation and migration (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…For this reason, a lot of research efforts are currently focusing on the development of materials with scavenging properties that can protect the wound bed from the mitochondrial damage inflicted by reactive oxygen species (ROS). In this sense, the recent work conducted by Xu et al involved the fabrication of a poly(d,L-lactide)-PEG-poly(d,L-lactide) (PLGA-PEG-PLGA) hydrogel for the encapsulation and controlled release of Prusian blue nanoparticles (PBNPs), a synthetic material that can mimic the ROS scavenging activity of naturally occurring antioxidant enzymes, such as peroxidase, catalase, and superoxide dismutase [ 72 ]. The thermosensitive properties of the prepared hydrogel allowed in situ gelation at physiological temperature.…”
Section: Hydrogel Wound Dressings For Dfu Treatmentmentioning
confidence: 99%